Diverging biological roles among human monocyte subsets in the context of tuberculosis infection - Balboa, Luciana (2015)
Circulating monocytes (Mo) play an essential role in the host immune response to chronic infections. We previously demonstrated that CD16pos Mo were expanded in TB (tuberculosis) patients, correlated with disease severity and were refractory to dendritic cell differentiation. In the present study, we investigated whether human Mo subsets (CD16neg and CD16pos) differed in their ability to influence the early inflammatory response against Mycobacterium tuberculosis. We first evaluated the capacity of the Mo subsets to migrate and engage a microbicidal response in vitro. Accordingly, CD16neg Mo were more prone to migrate in response to different mycobacteria-derived gradients, were more resistant to M. tuberculosis intracellular growth and produced higher reactive oxygen species than their CD16pos counterpart. To assess further the functional dichotomy among the human Mo subsets, we carried out an in vivo analysis by adapting a hybrid mouse model (SCID/Beige, where SCID is severe combined immunodeficient) to transfer each Mo subset, track their migratory fate during M. tuberculosis infection, and determine their impact on the host immune response. In M. tuberculosis-infected mice, the adoptively transferred CD16neg Mo displayed a higher lung migration index, induced a stronger pulmonary infiltration of murine leucocytes expressing pro- and anti-inflammatory cytokines, and significantly decreased the bacterial burden, in comparison with CD16pos Mo. Collectively, our results indicate that human Mo subsets display divergent biological roles in the context of M. tuberculosis infection, a scenario in which CD16neg Mo may contribute to the anti-mycobacterial immune response, whereas CD16pos Mo might promote microbial resilience, shedding light on a key aspect of the physiopathology of TB disease.